Knowledge, Information, and Creativity Support Systems 5th International Conference, KICSS 2010, Chiang Mai, Thailand, November 25-27, 2010, Revised Selected Papers - Theeramunkong, Thanaruk; Kunifuji, Susumu; Sornlertlamvanich, Virach; Nattee, Cholwich; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 5th International Conference on Knowledge, Information, and Creativity Support Systems, KCIS 2010, held in Chang Mai, Thailand, in November 2010. The 23 revised full papers presented were carefully reviewed and selected from 72 submissions. The papers cover a broad range of topics related to all knowledge science-related areas including creativity support, decision science, knowledge science, data mining, machine learning, databases, statistics, knowledge acquisition, automatic scientific discovery, data/knowledge visualization, and knowledge-based systems.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Information Systems; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Data Mining and Knowledge Discovery; Management of Computing and Information Systems